The Fusion Loops of the Initial Prefusion Conformation of Herpes Simplex Virus 1 Fusion Protein Point Toward the Membrane - Fontana, Juan; Atanasiu, Doina; Saw, Wan Ting; Gallagher, John R.; Cox, Reagan G.; Whitbeck, J. Charles; Brown, Lauren M.; Eisenberg, Roselyn J.; Cohen, Gary H. (mBio, 2017)
All enveloped viruses, including herpesviruses, must fuse their envelope with the host membrane to deliver their genomes into target cells, making this essential step subject to interference by antibodies and drugs. Viral fusion is mediated by a viral surface protein that transits from an initial prefusion conformation to a final postfusion conformation. Strikingly, the prefusion conformation of the herpesvirus fusion protein, gB, is poorly understood. Herpes simplex virus (HSV), a model system for herpesviruses, causes diseases ranging from mild skin lesions to serious encephalitis and neonatal infections. Using cryo-electron tomography and subtomogram averaging, we have characterized the structure of the prefusion conformation and fusion intermediates of HSV-1 gB. To this end, we have set up a system that generates microvesicles displaying full-length gB on their envelope. We confirmed proper folding of gB by nondenaturing electrophoresis-Western blotting with a panel of monoclonal antibodies (MAbs) covering all gB domains. To elucidate the arrangement of gB domains, we labeled them by using (i) mutagenesis to insert fluorescent proteins at specific positions, (ii) coexpression of gB with Fabs for a neutralizing MAb with known binding sites, and (iii) incubation of gB with an antibody directed against the fusion loops. Our results show that gB starts in a compact prefusion conformation with the fusion loops pointing toward the viral membrane and suggest, for the first time, a model for gB’s conformational rearrangements during fusion. These experiments further illustrate how neutralizing antibodies can interfere with the essential gB structural transitions that mediate viral entry and therefore infectivity. IMPORTANCE The herpesvirus family includes herpes simplex virus (HSV) and other human viruses that cause lifelong infections and a variety of diseases, like skin lesions, encephalitis, and cancers. As enveloped viruses, herpesviruses must fuse their envelope with the host membrane to start an infection. This process is mediated by a viral surface protein that transitions from an initial conformation (prefusion) to a final, more stable, conformation (postfusion). However, the prefusion conformation of the herpesvirus fusion protein (gB) is poorly understood. To elucidate the structure of the prefusion conformation of HSV type 1 gB, we have employed cryo-electron microscopy to study gB molecules expressed on the surface of vesicles. Using different approaches to label gB’s domains allowed us to model the structures of the prefusion and intermediate conformations of gB. Overall, our findings enhance our understanding of HSV fusion and lay the groundwork for the development of new ways to prevent and block HSV infection. The herpesvirus family includes herpes simplex virus (HSV) and other human viruses that cause lifelong infections and a variety of diseases, like skin lesions, encephalitis, and cancers. As enveloped viruses, herpesviruses must fuse their envelope with the host membrane to start an infection. This process is mediated by a viral surface protein that transitions from an initial conformation (prefusion) to a final, more stable, conformation (postfusion). However, the prefusion conformation of the herpesvirus fusion protein (gB) is poorly understood. To elucidate the structure of the prefusion conformation of HSV type 1 gB, we have employed cryo-electron microscopy to study gB molecules expressed on the surface of vesicles. Using different approaches to label gB’s domains allowed us to model the structures of the prefusion and intermediate conformations of gB. Overall, our findings enhance our understanding of HSV fusion and lay the groundwork for the development of new ways to prevent and block HSV infection.